Effect of empowerment-based interventions on self-efficacy and self-care capacity among patients with sickle cell disease: A randomized controlled trial - Zohour Ibrahim Rashwan; Hasan Abdali Khalil; Leena Mohamed Khonji; Gayathripriya Narayanan; Marwan Kamal Altheeb; Roseben Pradeep; Rajeswari Krishnasamy; Magda Mohamed Bayoumi (International Journal of Nursing Sciences)
Objective: This study aimed to investigate the effect of empowerment-based interventions on self-efficacy and self-care capacity among adults with sickle cell disease (SCD). Methods: A randomized control trial was conducted [NCT06296654]. A total of 76 patients were recruited by using a cluster sampling technique in the two health centers in Bahrain from February to May 2022 and randomly allocated to the intervention group (n = 38) or control group (n = 38). The intervention group received the empowerment-based intervention implemented through structured small-group discussion sessions, individualized consultations (5A model: assess, advise, agree, assist, and arrange), and follow-up sessions, while the control group received routine health education. The Sickle Cell Self-Efficacy Scale (SCSES) and the Appraisal of the Self-Care Agency Scale-Revised (ASA-R) were measured at baseline and one month after the intervention among two groups of patients. Results: A total of 68 patients completed the study (36 patients in the intervention group and 32 patients in the control group). After the intervention, the score of SCSES in the intervention group was 37.0 (35.0, 39.8) higher than the control group 28.0 (25.2, 32.0) (U = − 6.121, P < 0.001); the score of ASA-R in the intervention group was 61.0 (58.3, 65.0) higher than the control group 49.0 (43.3, 53.0) (U = 0.653, P < 0.001). Conclusion: Adopting the empowerment-based intervention using the 5As model effectively improves self-efficacy and self-care capacity among patients with SCD.